Dermatomyositis and HIV - Mamata Chand; Ashutossh Naaraayan; Kristine Sarmosyan; Jeffrey Lederman; Karen Weidenheim; Stephen Jesmajian (Greater Baltimore Medical Center, 2016)
HIV has been linked to several autoimmune disorders since its emergence in the 1980s. By affecting different cells and pathways in the immune system, HIV induces the development of certain autoimmune diseases while prohibiting the emergence of others. Dermatomyositis has been rarely described in patients with HIV. We present a case of dermatomyositis in a patient with HIV and explore the pathogenesis of autoimmune disorders in HIV focusing on dermatomyositis.